Determinant of marital satisfaction among young couples in Lagos state, Nigeria (2015)
Correlational survey design was adopted to examine the predictive influence of psychological and social factors on marital satisfaction of young couples in Lagos state. Representative sample size of 682 young couples completed measures regarding personality trait, religiosity; parental influence and marital satisfaction. The hypothesized variables have correlation coefficients ranging from r-.123 to .519 with marital satisfaction. Multivariate Regression Analyses indicated that the contribution of the independent variables to the prediction of the dependent variable was significant [F (5. 676] =14.49; p<. 001). They jointly accounted for about 29.5% variation in the prediction of marital satisfaction. Religiosity had the highest contribution (β =. 186, t=5.34; P < 05) while parental influence and gender were not potent in predicting marital satisfaction. The study provides empirical evidence to suggest that psychological and social factors have relationship with marital satisfaction in varying dimensions.